ANALISIS HADIS DALAM PERSPEKTIF EKONOMI ISLAM - Nasir, Muhammad (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
This research examines the principles of Islamic economics taught in the hadiths of Prophet Muhammad (SAW), focusing on their relevance and implementation in the context of the modern economy. The hadiths, as the second source of law in Islam, provide clear guidelines on honesty, justice, prohibition of usury, social concern, and investment ethics. Through thematic analysis of several hadiths, this research identifies that these principles not only form the foundation of the Islamic economic system but are also relevant in creating an economic system that is fair, ethical, and sustainable. The methodology of this research uses a qualitative approach with a descriptive-analytical method (Fiantika, 2022). Data Collection: Primary Data: Relevant hadiths related to Islamic economic principles are taken from major hadith collections such as Sahih Bukhari, Sahih Muslim, Sunan Abu Dawood, Sunan Tirmidhi. Secondary Data: Literature related to Islamic economics, books, journal articles. Data Analysis Techniques: Thematic Analysis: Hadiths are categorized based on main themes such as honesty, justice, prohibition of usury, social concern, and investment ethics. The findings show that by following the Islamic economic principles derived from the hadiths, the economy can become more just, stable, and sustainable, ultimately building a more prosperous society. This application is significant not only from a religious perspective but also in constructing a more humane and just economy.